Teaching in higher education: criteria and standards of quality in Chile - Pérez Carvajal, Alejandro; Catalán Cueto, Juan Pablo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article reveals the criteria and quality standards for the institutional accre- ditation of the university subsystem, Law 21,091. It asks: How is the dimension of teaching and the training process understood from the criteria and quality stan- dards for institutional accreditation? The objective is to analyze the characteristics that are manifested explicitly and implicitly on this dimension. The methodology is a documentary study from direct and indirect sources. The conclusions express the need to disaggregate the elements concerning criteria 1, 2, 3 and 4 of the Teaching Dimension and Results of the Training Process.